Trello y su incidencia en el aprendizaje colaborativo de los estudiantes de bachillerato técnico de informática, sección matutina de la Unidad Educativa Eugenio Espejo, periodo académico Octubre 2024 Marzo 2025. - Aviles Mayorga, Selenia Mirela (2025)
The objective of this research work is to propose the use of Trello to strengthen the learning of the students of the technical baccalaureate in computer science of the Eugenio Espejo Educational Unit, during the academic period October 2024 - March 2025. It seeks to determine how Trello, a project management platform, can strengthen competencies such as communication, organization, collective responsibility and teamwork in a technical educational context. The research employs a mixed approach (qualitative and quantitative) to collect data through student surveys, combining descriptive, explanatory and applied methodologies. The research project is structured in four chapters that address the introduction, theoretical framework, methodology and a timeline with budget. International and national background on the use of digital platforms such as Trello in education is highlighted, emphasizing its positive impact on collaboration, motivation and academic performance. Likewise, the characteristics, benefits and challenges of Trello are described, as well as the advantages and disadvantages of collaborative learning. It is hypothesized that the use of Trello will contribute significantly to students' collaborative learning. This research includes an experimental and propositional design, with a sample of 80 students of first, second and third year of technical high school. The main instruments are digital surveys and bibliographic consultations. The results will be analyzed using tools such as Google Forms and Excel, and it is expected that the use of Trello will foster critical, reflective and collaborative skills. The implementation of our proposal is a task management tool based on collaborative boards to improve organization in the students of the Eugenio Espejo Educational Unit.